A Survey of Statistical Capstone Projects. Issue 3 (1st September 2016) - Martonosi, Susan E.; Williams, Talithia D.
ABSTRACT: In this article, we highlight the advantages of incorporating a statistical capstone experience in the undergraduate curriculum, where students perform an in-depth analysis of real-world data. Capstone experiences develop statistical thinking by allowing students to engage in a consulting-like experience that requires skills outside the scope of traditional courses: defining a complex problem, analyzing data, building a strong team, and communicating effectively. We describe the pedagogical benefits as they relate to improved student outcomes and prospective job and graduate school placement, and we classify statistical capstones into four groups: standalone capstone projects, statistical consultancies, capstone projects embedded in an advanced statistics methodology course, and instruction-focused capstone courses. This article serves as a guide for educators seeking to implement an enriching capstone experience in their undergraduate mathematics or statistics curriculum to better prepare students for industrial and academic careers in data science.